2020
DOI: 10.1016/j.fertnstert.2020.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Identification and treatment of men with phospholipase Cζ–defective spermatozoa

Abstract: Objective: To identify and treat the gamete responsible for complete fertilization failure with intracytoplasmic sperm injection (ICSI) using a newly proposed assisted gamete treatment (AGT). Design: Prospective cohort study. Setting: Center for reproductive medicine. Patient(s): One-hundred and fourteen couples with an adequate number of spermatozoa for ICSI and a fertilization rate of %10%, after controlling for maternal age. Intervention(s): Couples with an oocyte-related oocyte activation deficiency (OAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Couples with a normal OASCF who were continuing treatment at our center ( n = 4) underwent conventional ICSI, while consenting couples with an OASCF deficiency ( n = 7) were treated by ICSI with AGT in their subsequent cycles (Fig. 1 ) [ 20 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Couples with a normal OASCF who were continuing treatment at our center ( n = 4) underwent conventional ICSI, while consenting couples with an OASCF deficiency ( n = 7) were treated by ICSI with AGT in their subsequent cycles (Fig. 1 ) [ 20 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The use of oocyte activation with ICSI has been shown to achieve fertilization and successful pregnancies, even in patients with the most severe cases of globozoospermia [ 5 ]. However, its application has recently been shown to be necessary only in cases with a confirmed sperm-related, oocyte-activating deficiency [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the predictive potential of PLCζ immunostaining and immunoblotting was questionable. However, two very recent articles have proposed new algorithms using PLCζ immunostaining assay for the clinical management of patients suffering from FF after ICSI, which appear to be very useful to determine the responsible gamete and to predict the efficacy of AOA in the next treatment [51,148].…”
Section: Gene Expression Analysis Protein Localization and Quantification Assaysmentioning
confidence: 99%
“…The leading cause for TFF after ICSI has been attributed to oocyte activation de ciencies (OADs), which can be related to sperm or oocyte factors. Studies have shown that AOA can be helpful to couples who have clear sperm-related OAD [2,4,6].…”
Section: Introductionmentioning
confidence: 99%